The combined effects of binder addition and different sintering methods on the mechanical properties of bovine hydroxyapatite - Minim, P. R.; de Azevedo-Silva, L. J.; Ferrairo, B. M.; Pereira, L. F.; Goulart, C. A. [UNESP]; Monteiro-Sousa, R. S.; Lisboa Filho, P. N. [UNESP]; Fortulan, C. A.; Salomão, R.; Borges, A. F.S.; Rubo, J. H. (Elsevier, 2023)
Hydroxyapatite (HA) from bovine bones has been used as a biomaterial in dentistry due to its biocompatibility and bioactivity. However, dense HA bioceramics still present inadequate properties for applications that require high mechanical performance, such as infrastructure. Microstructural reinforcements and control of ceramic processing steps are methods to improve these shortcomings. The present study assessed the effects of polyvinyl butyral (PVB) addition in combination with two sintering methodologies (2-step and conventional), on the mechanical properties of polycrystalline bovine HA bioceramics. The samples were divided into four groups (with 15 samples per group): conventional sintering with binder (HBC) and without binder (HWC) and 2-step sintering with (HB2) and without binder (HW2). HA was extracted from bovine bones, turned into nanoparticles in a ball mill, and subjected to uniaxial and isostatic pressing into discs, according to ISO 6872 standards. All groups were characterized by x-ray diffractometry (XRD), differential thermal analysis (DTA) and Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and relative density. Besides, mechanical analyses (biaxial flexural strength (BFS) and modulus of elasticity) were also performed. The characterization results demonstrated that adding agglutinants or the sintering method did not affect HA's chemical and structural characteristics. Even so, the HWC group showed the highest mechanical values for BFS and modulus of elasticity being 109.0 (98.0; 117.0) MPa and 105.17 ± 14.65 GPa, respectively. The HA ceramics submitted to conventional sintering and without the addition of binders achieved better mechanical properties than the other groups. The impacts of each variable were discussed and correlated to the final microstructures and mechanical properties.
Keywords: Apatite; Biomedical applications; Precursors: organic; Sintering